The Assessment of Topography Model Based on Global Digital Elevation Model (DEM) in Selangor - Noorzamani, Mohamad Amirul Danial; Azlan, Muhammad Seri Hidayat; Jaliasna, Nournaqie Afsar; Yazid, Nornajihah Mohammad (Multidisciplinary Applied Research and Innovation, 2025)
Selangor, a state in Malaysia, frequently experiences floods due to its topography and driven by consistent rainfall in the region. An accurate topographic data is crucial for effective flood management and natural disaster management. In the current era of technology, the exploration risk mapping will be easier by applying the Geographic Information System (GIS) based on Digital Elevation Model (DEM). Thus, this study aims to evaluate the accuracy of topography model based on DEMs in Selangor using GNSS Levelling. Next, select the DEMs for the Selangor and examine the most suitable DEMs based on SRTM, ASTER, TanDEM-X and verified with GNSS Levelling data. Then, map the topography in Selangor based on DEM data that contributes to risk assessment using MATLAB software. The result indicate that TanDEM-X has the lowest standard and the highest correlation with 2.365m and 0.9981m, respectively. As a result, TanDEM-X is selected as an appropriate DEM for Selangor, and it represents a significant impact for the next study related to geoid computation, floods, sea level rise and many more.